The basics of chemistry - Myers, Richard L. (Richard Leroy), 1951- (Westport, CT : Greenwood Press, 2003)
An introduction to chemistry that offers an overview of the field's main theories, topics, and ideas, its history, and key figures.
Includes bibliographical references (p. [363]-364) and indexes.
Choice.
Library Journal.
Wilson's Senior High School.
Choice, February 2004.
Library Journal, October 2003.
Keywords: Chemistry; Chemistry